Evaluating the family adoption program as a noncommunicable disease surveillance tool in India: A systematic review - Urvish Joshi; Sharon Baisil (Asian Journal of Medical Sciences, 2025)
India faces a rising noncommunicable disease (NCD) burden, highlighting the need for effective surveillance. The family adoption program (FAP), a medical education initiative engaging students with communities, presents potential for data collection. This systematic review evaluated FAP’s effectiveness as an NCD surveillance tool. Following PRISMA guidelines, relevant databases were searched (2020–2025) for FAP studies reporting prevalence data on obesity, anemia, diabetes, or hypertension. Three FAP studies, including the National Medical Commission FAP Survey Report 2024, were compared against five national reports. While FAP-derived obesity prevalence closely matched National Family Health Survey −5 data, significant discrepancies were found for hypertension, anemia, and diabetes estimates. These were attributed to methodological inconsistencies, lack of population representativeness, and variations in training and equipment calibration within FAP compared to standardized national surveys. FAP data showed moderate–high bias risk. Although valuable for experiential learning and local health initiatives, FAP currently lacks the methodological rigor and representativeness for reliable national/state NCD surveillance without significant standardization and quality improvements.